RANCANG BANGUN WEBSITE PENGELOLAAN BUKU DIGITAL BERBASIS NATURAL LANGUAGE PROCESSING (NLP) - Rangga Wahyu Pratama; Paskah Abadi Simanullang; Peter Tymoty Hutabarat; Revidamurti Daulay; Adidtya Perdana (Jurnal Teknologi Informasi dan Komputer, 2025)
A digital book management system has become a crucial solution in the digital era, helping users efficiently organize and search their book collections. In the context of information technology advancements, the demand for an integrated platform that can store book data and provide easy access through metadata-based search features is increasing. However, the main challenge lies in the absence of a system that supports automatic information extraction from digital book files and searches based on criteria such as title, language, or topic. To address this issue, this study employs the Research and Development (R&D) method to design the system, a literature review to analyze NLP technology, and observations to understand user needs. The research results in an application built with PHP, MySQL, and Python (NLP), featuring file uploads, automatic metadata extraction, search based on specific criteria, and user profile management. The study concludes that the developed system provides a practical and efficient solution for digital book management, with a modular design that supports scalability and further development.